Circadian Rhythm Disruption in Alzheimer’s Disease: Molecular Mechanisms, Clinical Implications, and Therapeutic Approaches - Romi Rajput; Anjali Sharma; Vishnu Mittal; Devkant Sharma (Current Neurovascular Research, 2026)
Introduction:: Alzheimer's Disease (AD) is a progressive neurological disorder characterized by unusual behavior, memory deterioration, and a decline in cognitive abilities. A growing body of research indicates that circadian rhythm disturbances play a crucial role in the pathophysiology of AD, impacting both molecular processes and clinical outcomes. This review critically evaluates the molecular interplay between circadian rhythm disruption and AD pathology, explores its impact on clinical manifestations and disease progression, and assesses emerging diagnostic and therapeutic strategies to restore circadian regulation and improve patient outcomes. Methods:: A thorough analysis of recent research on molecular clock genes (CLOCK, BMAL1, PER, and CRY) and their roles in regulating hormone rhythms, metabolism, and sleep-wake cycles was conducted. Research on technology-based methods, therapeutic treatments, and circadian biomarkers was assessed to determine their applicability in AD. Results:: Circadian gene dysregulation was found to exacerbate tau hyperphosphorylation, amyloid- β accumulation, oxidative stress, and neuroinflammation. Clinically, circadian disruption manifests itself as mood disorders, sleep-wake abnormalities, and accelerated cognitive deterioration. Discussion:: Light therapy, melatonin supplements, chrono-pharmacology, and behavioural techniques are among the interventions that have shown promise in restoring rhythm stability. Wearables, smart lighting, neuromodulation, and multi-omics modelling are examples of technological advancements that increase the range of diagnostic and treatment possibilities. Conclusion:: Patient heterogeneity, translational gaps, and a lack of mechanistic knowledge continue to pose difficulties despite progress. To enhance AD outcomes, future research should focus on integrated, customized therapies that target the circadian rhythm.